GOVERNMENT EMERGENCY ORDINANCE NO. 44/2008 BETWEEN INNOVATION AND CHANGE - Gabriela FIERBINŢEANU (Challenges of the Knowledge Society)
The evolution of the regulations standardizing the performance of the economic activity by the natural persons, i.e. associations of family members, is one showing the need for a continuous adaptation to the needs of the society. The proposal contained by this work is far from criticising the regulation manner of these activities, as it rather intends to identify solutions for the practical situations which are sometimes preventing or questioning the access to these forms of organization or the manner of performing the activity.